Enriching the information systems curriculum to enable digital innovation capacity - van den Berg, C.L. (South African Journal of Higher Education, 2018)
The diffusion of digital infrastructure is opening up multiple opportunities for innovations to transform business and society. The overall purpose of Information Systems (IS) education is to equip students to use technology to improve the effectiveness of business, the environment and society, and digital innovation lies at the heart of this transformation. Information Systems students are in the fortunate position that they are instructed in both Information Technology (IT) and business, and therefore can be taught to identify the value of advances in technology to meet an unmet organisational or societal need. This requires flexibility and the ability to collaborate, which requires skills such as problem solving, communication, team work, multicultural openness, adaptability, innovation and creativity. Graduates should therefore play a leading role as the innovators of the future. The teaching and learning environment needs to prepare them for this uncertain, complex and ambiguous world, in which they move beyond the current horizons of knowledge and skills within a specific discipline. This paper explores the complexities of our higher education environment, coupled with the explosion of digital technologies and, at the centre, the students and their well-being. The intention is to explore the skills required to enhance the capability of IS students to participate in, and ultimately orchestrate, digital transformation in business and society. A design-based research (DBR) approach was applied in a mixed-methods design via three iterations during 2016 and 2017. The study produced scientific outputs resulting in eight design principles to capacitate students for the future world of work.